Serological prevalence of Leptospira icterohaemorrhagiae, in canines of the municipality of Lejanías, Meta (Colombia) - Cárdenas-García, Darío; Suárez-Suárez, Diana Carolina; Ortiz-González, Arwin René; Galindo-Ariza, René Alejandro; Moreno Quijano, Angie Paola (Spei Domus, 2019)
Introduction: Leptospirosis is a zoonotic disease, produced by a spirochete bacterium (Leptospira spp) that has more than 200 serovars, which produces kidney damage. The objective of the study was to determine the serological prevalence of Leptospira icterohaemorrhagiae in female canines in the Municipality of Lejanías, Meta-Colombia.Methodology: With a descriptive and association approach, 100 female dogs from the rural area and the urban area of ​​the municipality of Lejanías, Meta-Colombia, were studied. They were taken for a sterilization campaign carried out in November 2017. Previous semiological examination of the individuals was carried out. He took a blood sample for serological study using the microscopic agglutination (MAT) technique for Leptospira icterohaemorrhagiae.Results: A seroprevalence of 1 % positivity to L. icterohaemorrhagiae at the 1/200 dilution was evidenced. No association was found between the age factor or rural or urban origin. However, with the chi square technique, an association was found with the factors of temperature and color of mucous membranes (pale, icteric, cyanotic, hyperemic or pink).Conclusions: This seropositivity value suggests a possible low circulation and presence of the agent Leptospira icterohaemorrhagiae in the study area. However, other investigations that take into account the variables studied could contribute to explain the possible reasons for these relatively low values ​​when compared with the available results.
Keywords: canine diseases; epidemiology; leptospirosis; prevalence; zoonoses; pathology